Q: 3x plus 5 x plus 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x+5<x+11 3x<6 x<2

Because (x plus 3x) is 4x, and (-5 + 11) is 6.

-5 + -3x + -x + 16-4x + 11

3x+4=-11 3x=-15 x=-5

2x-5=3x+6 -5-6=3x-2x -11=x x=-11

Related questions

3x+5<x+11 3x<6 x<2

Because (x plus 3x) is 4x, and (-5 + 11) is 6.

-5 + -3x + -x + 16-4x + 11

3x+4=-11 3x=-15 x=-5

-4x + 5 + 3x + 6 = -x + 11

2x-5=3x+6 -5-6=3x-2x -11=x x=-11

It is equivalent to: 3x+6+5 = 3x+11

When x = 2, 3x + 5 = 11.

Where is y in the first equation, you put its equivalent (=) -3x + 11 The first equation is then transformed into: 3x + 2*(-3x + 11) = 7. Then you get: 3x + (-6x) + 2*11 = 7 <=> -3x + 22 = 7 <=> 22 - 7 = 3x <=> 3x = 15 <=> x = 15/3 <=> x = 5. Then you substitute the x in the second equation by its equivalent so, (x = 5) y = -3*x + 11 <=> y = -3*5 + 11 <=> y = -15 + 11 <=> y = -4. x = 5. y = -4.

x+5 = 3x+15 x-3x = 15-5 -2x = 10 x = -5

3x + 11 = x + 3 2x = -8 x = -4

3x - 11 = x + 5subtract x from both sides:3x - x - 11 = x - x +52x - 11 = 5add 11 to both sides:2x - 11 + 11 = 5+112x = 16divide both sides by 2 to solve for x:2x/2 = 16/2x = 8